Ancestral knowledge and academic knowledge: A commitment to interculturality in the tourism development of Colta and Guamote - Pomaina Pilamunga, Bacilio Segundo (2024)
In accordance with global demands, UNEMI has the linkage project titled “Strengthening tourism skills in indigenous communities” implemented in the communities of Colta and Guamote, Chimborazo; Therefore, the objective was to systematize the community experiences that emerged in the linkage project in the aforementioned context during the period 2021-2022 through theoretical foundations and oral stories to demonstrate knowledge from a holistic vision of local knowledge based on ethnotourism. We worked with a mixed descriptive approach and case study design. The collection of information was carried out using the survey technique that yielded quantitative results and the interview technique that generated qualitative information. The results highlighted the importance, advantages and challenges of linkage projects. It is concluded that this type of projects allows creating opportunities to improve the comprehensive development of communities.